Fenomena Fonetik: Tantangan Pelafalan Huruf 'e' oleh Penutur Asing Program Darmasiswa : Phonetic Phenomenon: Challenges in Pronunciation of the Letter 'e' by Foreign Speakers Darmasiswa Program - Sucipta, I Made Darma; Widanta, I Made Rai Jaya (Information Technology and Science(ITScience), 2025)
Learning Indonesian for foreign speakers, especially participants in the Darmasiswa program, presents complex phonetic challenges. One of the main difficulties lies in the pronunciation of the vowel 'e', ??which has three sound variations: [e], [?], and [?]. This difference often confuses learners because not all mother tongues have similar vowel systems. This study aims to describe the types of pronunciation errors associated with the letter 'e', identify the factors that cause them, and offer relevant phonetic learning strategies. The study employed a qualitative descriptive approach, utilizing observation, interviews, and documentation techniques, with four foreign learners participating in the Darmasiswa Program at Bali State Polytechnic. The results showed that approximately 55% of words containing the vowel 'e' were mispronounced. The most dominant error was the substitution of the sound [?] for [e], which was caused by the influence of the mother tongue, phonological limitations, and the lack of phonetic teaching media. The application of diacritical marks (é = [e], è = [?], ê = [?]) has been proven to help learners understand pronunciation differences more accurately. This strategy not only improves articulation skills but also enhances learners' phonetic perception and linguistic awareness of the Indonesian language sound system. Thus, this study emphasizes the importance of developing phonetic-based teaching media and integrating technology, such as audio or QR codes, into BIPA learning, so that foreign learners can pronounce the vowel 'e' correctly and communicate effectively and contextually.